PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIALMELALUI KOMITMEN ORGANISASI DANBUDGETEMPHASIS SEBAGAI VARIABEL INTERVENING (Studi Kasus pada SKPD PemerintahKabupaten Boyolali) - Hidayat Setiadi; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of budgetary participation to managerial performance relationship in a public sector organization. It also attempts to examine whether organization commitment and budget emphasis mediate the budgetary participation and managerial performance relationship.This study used survey questionnaires method that was implemented toward managers in a public sector organization. Questionnaires were given to 133 respondents. From a total of 101 questionnaires which were received back, 90 questionnaires were able to be used for the research, so its response rate is 68%. A path analysis was utilized to examine the direct and indirect effects of budgetary participation toward managerial performance. The result of research analysis shows that budgetary participation has a direct effect toward managerial performance, commitment organization and budget emphasis. Besides, budgetary participation also has an indirect effect toward managerial performance via organization commitment and budget emphasis as an intervening variable.